Perception of Teachers in Math Learning using Problem Based Learning Model - Broto Apriliyanto; Dewi Retno Sari S; Riyadi Riyadi (Pancaran Pendidikan, 2018)
Learning process determines the improvement of students’ learning achievements. Selection of an appropriate learning experience is the task of the teacher as a facilitator in charge of providing a supportive learning environment for the students. This study aims to determine the perception of teachers after implementing learning using Problem Based Learning model. The subject of this research is the Math teachers at State Senior High School 1 Wuryantoro, Wonogiri Regency, Academic Year 2017/2018. Data are collected using interviews to find out teachers' perceptions of the implementation of Problem Based Learning model. The result shows that the Probem Based Learning model make it easier for teachers to learn in the classroom because students are more interested and active, but teachers are often constrained in constructing contextual problems that can connect with the intended concept. Limited time allocation is also a constraint of implementing learning using Problem Based Learning.